An analysis of the literature addressing tonsillectomy knowledge gaps. (December 2018) - Cooper, Craig M.; Checketts, Jake X.; Brame, Lacy; Gray, Harrison; Downs, Jaye Bea; Vassar, Matt
Abstract: Importance: The ability of clinical practice guidelines to improve patient outcomes depends on the quality of evidence that they are built upon. Research into tonsillectomy in children is lacking, and the gaps in evidence were identified by guideline authors. Objective: The objective of this study is to evaluate the extent that new research is addressing the gaps identified in the AAO-HNS Tonsillectomy in Children Guideline. Design: For each recommendation in the AAO-HNS guideline Tonsillectomy In Children, we created PICO (Participants, Intervention, Comparator, Outcome) questions and search strings. PubMed was searched to locate studies undertaken after the final literature search performed by the AAO-HNS work group. These studies were then extracted and analyzed. Setting: This study is relevant to all invested in focusing otolaryngological research on questions which currently lack strong evidence. Participants: Trials in tonsillectomy that started after the development of the AAO-HNS clinical practice guidelines. Main outcome measures: The main outcome measures of this study is the extent to which tonsillectomy research is addressing the evidence gaps listed in the clinical practice guideline. Results: Of the 2519 studies included in our sample, 276 (11%) were relevant to the 18 recommendations made within the Tonsillectomy in Pediatric Patients clinical practice guideline. All but one of the recommendations was met by at least one study. Conclusions: and Relevance: Our findings indicate that knowledge gaps within the guideline at publication may have since been addressed and a guideline update may thus be warranted. Level of evidence: NA.